Audit Judgment in Task Complexity: The Role of Audit Expertise and Big Five Personality - T, Sutrisno; Prihatiningtia, Yeney Widya; Rizkiah, Galuh Mutiara (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to examine the influence of audit expertise and task complexity on audit judgment by incorporating the Big Five personality traits as moderating variables. The research is motivated by the low quality of audit judgment in the public sector, as reflected in recurring audit findings, including those at the Ministry of Public Works and Housing (PUPR). We collected data using a quantitative causal approach through a questionnaire survey involving 164 auditors at the Inspectorate General of the Ministry of PUPR. The analysis technique applied was Partial Least Squares-Structural Equation Modeling (PLS-SEM) using SmartPLS. The results indicate that both audit expertise and task complexity have a significant positive effect on audit judgment. The personality traits of conscientiousness, extraversion, and openness to experience strengthen these relationships, while neuroticism weakens them. Meanwhile, agreeableness moderates only the relationship between audit expertise and audit judgment, but not the relationship between task complexity and audit judgment. This study contributes to the broader understanding of the auditor’s personality role in improving audit judgment quality, particularly among internal auditors in the public sector, an area that has received limited research attention.